Paradigma Filsafat John Dewey dalam Pendidikan Inklusi - Ila Khayati Muflikhah; Abdul Khobir (BADAN PENERBIT STIEPARI PRESS, 2023)
Education is a right for all citizens without discrimination. Everyone has the right to a decent living, including children with special needs. However, education in our country still underestimates the presence of children with disabilities. Many educational institutions refuse to accept children with special needs (ABK). In line with Dewey's thoughts, a Western pragmatic philosopher said that every boy and girl has the same right to get a decent education. Strengthened State law article 31 paragraph 1 concerning the right of all citizens to receive education. This research aims to analyze the relevance of Dewey's thoughts to inclusive education and to educate readers that children with special needs also have the right to receive adequate education. This research uses a library study method by collecting various information through journals, books, newspapers, and other media. The results of this research show the relevance of John Dewey's thinking to inclusive education